The Combined Inhibitory Effect of the Adenosine A1 and Cannabinoid CB1 Receptors on cAMP Accumulation in the Hippocampus Is Additive and Independent of A1 Receptor Desensitization. (18th January 2015) - Serpa, André; Correia, Sara; Ribeiro, Joaquim A.; Sebastião, Ana M.; Cascalheira, José F.
Abstract : Adenosine A1 and cannabinoid CB1 receptors are highly expressed in hippocampus where they trigger similar transduction pathways. We investigated how the combined acute activation of A1 and CB1 receptors modulates cAMP accumulation in rat hippocampal slices. The CB1 agonist WIN55212-2 (0.3–30 μ M) decreased forskolin-stimulated cAMP accumulation with an EC50 of 6.6 ± 2.7 μ M and an E max ⁡ of 31% ± 2%, whereas for the A1 agonist, N 6 -cyclopentyladenosine (CPA, 10–150 nM), an EC50 of 35 ± 19 nM, and an E max ⁡ of 29% ± 5 were obtained. The combined inhibitory effect of WIN55212-2 (30 μ M) and CPA (100 nM) on cAMP accumulation was 41% ± 6% (n = 4 ), which did not differ (P > 0.7 ) from the sum of the individual effects of each agonist (43% ± 8%) but was different (P < 0.05 ) from the effects of CPA or WIN55212-2 alone. Preincubation with CPA (100 nM) for 95 min caused desensitization of adenosine A1 activity, which did not modify the effect of WIN55212-2 (30 μ M) on cAMP accumulation. In conclusion, the combined effect of CB1 and A1 receptors on cAMP formation is additive and CB1 receptor activity is not affected by short-term A1 receptor desensitization.